The Analysis Of Fast Food Marketing Strategy At Kentucky Fried Chicken Restaurant Tomohon - Silvana Kalangi, Jola; R. Kalalo, Rieneke; A.P.J. Pangkey, Deisy; Lintong, Elsje; Evly R.I. Liow, Festus (Politeknik APP Jakarta, 2024)
The development of fast food restaurant business services is increased and expanded. This fast food business competes on quality, price, and service. Kentucky Fried Chicken (KFC) restaurant in Tomohon City is competing to serve fast food that pampers its consumers. Thus, departing from this problem, the purpose of this study is to determine the right marketing strategy for fast food products to satisfy the consumer desires. Method of analysis used in this research is the quantitative method with analytical descriptive approach. The results show that KFC restaurant in Tomohon has made strategic efforts with product safety compliance that maintains the high quality standards, creating innovation and having qualified Human Resources (HR). The quality of service to consumers is well maintained. The restaurant uses the Customer Service Excellence (CHAMPS). CHAMPS is applied to ensure the restaurant Cleanliness, Hospitality, Accuracy in receiving and preparing orders, Maintenance of best facility, Products with high quality, and Speed with service. The conclusion states that the restaurant needs to maintain the successful performance of fast food business in its competition. Furthermore, the restaurant should remain obedient to their company management by conforming the laws and regulations and realizing the company's vision and mission as well.